Molecular phylogeny of Convallarioideae (Asparagaceae), with emphasis on Vietnamese species - Le, Thi Mai Linh; Ly, Ngoc Sam; Pham, Van The; Nguyen, Phuong Hanh; Tran, Duc Binh; Dong, Lina; Averyanov, Leonid V.; Tanaka, Noriyuki; Nguyen, Sinh Khang (Academia Journal of Biology, 2024)
With the aim of inferring phylogenetic relationships among 86 species (including 45 species from Vietnam) mostly of the subfamily Convallarioideae (=Nolinoideae) (Asparagaceae sensu APG IV), we analyzed their chloroplast DNA sequences (rbcL and trnL-F) by both Bayesian inference (BI) and maximum likelihood (ML) methods. Our dataset included six of the seven tribes classified in this subfamily; Convallarieae, Dracaeneae, Liriopeae Nolineae, Polygonateae and Rusceae (Eriospermeae not examined). Our study supported the sisterhood between Convallarioideae and Asparagoideae and the monophyly of all the tribes except Polygonateae. Within the Convallarioideae we examined, Dracaena formed the basalmost clade. Theropogon did not positively nest in any of the tribes including Convallarieae in which it had often been classified. It was weakly defined as the second basalmost branch. Ruscus (Rusceae) nested in Polygonateae as the sister to Maianthemum, hence Polygonateae was recognized here as paraphyletic. Nolineae was discordant in position between BI and ML analyses, probably reflecting the limited molecular markers we examined. In both BI and ML analyses, all genera of Liriopeae and Convallarieae were monophyletic and their intergeneric relationships were consistent. In Liriopeae, Liriope was sister to the clade of Ophiopogon + Peliosanthes. In Convallarieae, Aspidistra + Tupistra formed the sister clade to Reineckea + Rohdea. Interspecific relationships within these genera were, however, not clearly resolved, except for several pairs of sister species. We also briefly discussed some of the resultant phylogenetic relationships from the morphological and/or evolutionary aspects.